Interethnic relations in the Steppe region in 19th–early 20th centuries on pages of periodicals - E. P. Ivanov (Омский научный вестник: Серия "Общество. История. Современность", 2020)
The article is devoted to the establishment and development of inter-ethnic relations between the inhabitants of the Russian Empire and the indigenous people of the Steppe Territory. The article deals with the dynamics of the transformation of the image of a region reflected in the Russian periodical press of the XIX–early XX centuries. It is shown that the reflection in the press of the character of RussianKyrgyz inter-ethnic relations was the most important factor in the formation of the image of the Steppe Territory in the eyes of Russian inhabitants